Method for preparing graphite carburant by utilizing raw carbon fragments
By cleaning, crushing and pickling the carbon raw crushing, combined with high-temperature graphitization treatment, high-quality graphite carbon enhancers are prepared, which solves the problems of complex processes and high costs in the existing technology, and achieves efficient utilization of resources and sustainable environmental development.
Patent Information
- Application Number
- CN202411774087.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing graphite carbon enhancer has complex preparation processes, harsh reaction conditions, and high manufacturing costs, making it difficult to effectively utilize waste materials such as carbon crushing.
The carbon crushing is processed through cleaning, crushing, pickling and drying, and the impurities are removed and their purity is improved. Then, it is mixed with purified graphite powder, carbon black powder and SiC powder, and a binder and flux promoter are added. After high-temperature graphitization, a high-quality graphite carbon enhancer is prepared.
The process flow is simplified, the harshness of reaction conditions is reduced, the manufacturing cost is reduced, and the economic value of carbon crushing is significantly improved. The prepared graphite carbon enhancer has high fixed carbon content, low impurity content, and high carbon absorption rate, which meets the needs of high-quality steel smelting.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon material processing, in particular to a method for preparing a graphite recarburizer by utilizing raw carbon. Background Art
[0002] In the steelmaking process, it is necessary to add carbon to the molten steel in the ladle to improve the performance of the steel. There are many types of traditional carburizers, mainly including petroleum coke, activated carbon carburizer, calcined coal carburizer and graphite carburizer. Among them, petroleum coke, activated carbon carburizer and calcined coal carburizer have many defects, such as a wide variety of impurities, high impurity content, relatively low fixed carbon content and high water content. In the process of steelmaking carburization, the melting performance of these carburizers is poor, resulting in unsatisfactory carbon absorption rate or carbon recovery rate. Compared with the aforementioned carburizers, artificial graphite carburizer stands out for its high degree of graphitization, high carbon content, high density, excellent purity and low impurity content. It is easily absorbed by molten iron, and the carbon absorption rate can be as high as 90% or more, showing an excellent carburization effect, which can meet the needs of high-quality steel smelting. Therefore, in the metallurgical industry, artificial graphite carburizer has become the best carburizer currently used.
[0003] In the prior art, the preparation of artificial graphite recarburizer mainly uses powdered high-quality calcined petroleum coke as the main raw material and asphalt as a binder. In addition, a small amount of other auxiliary materials are added. The final product is obtained by uniformly mixing these raw materials and auxiliary materials, pressing and forming them, and performing high-temperature graphitization treatment in a non-oxidizing atmosphere at 2500-3000°C. However, this process has the defects of complex manufacturing process, harsh reaction conditions and high manufacturing cost. Therefore, in order to reduce production costs, recyclable materials such as chips, waste electrodes and graphite blocks generated when manufacturing graphite electrodes are usually used as artificial graphite recarburizers for steel smelting and casting. However, before use, these materials need to be crushed to a particle size suitable for smelting.
[0004] Green Scrap refers to the waste products produced due to unqualified technical inspections during the carbon product pressing process, as well as the paste residue dropped during the molding process and the residual heads cut off during extrusion molding. They are usually treated as residual waste materials during the production process. Generally speaking, although green scrap materials contain a high proportion of carbon elements, their carbon structure is relatively loose, which makes them have certain limitations in industrial applications. Despite this, green scrap still has certain utilization value in industry. They are usually used as low-value fuels or added as ingredients to products of the same formula to reduce production costs. It is worth noting that the carbon elements contained in certain types of green scrap actually have a high potential value. If it can be used as a raw material component to produce high-value-added graphite recarburizers through improved processes, it will not only significantly improve the economic value of green scrap, but also broaden its scope of application in the industrial field, thereby achieving efficient utilization of resources and sustainable development of the environment. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a method for preparing a graphite recarburizer by using raw carbon to solve the shortcomings of the above-mentioned background technology.
[0006] The technical problem solved by the present invention is achieved by adopting the following technical solutions:
[0007] A method for preparing a graphite recarburizer using raw carbon powder comprises the following steps:
[0008] S1, washing the collected raw carbon, and drying it after washing to remove floating dust and surface impurities;
[0009] S2, crushing the dried carbon raw material into crushed materials, firstly using dilute hydrochloric acid or dilute sulfuric acid for primary pickling, after pickling, rinsing with water and solid-liquid separation, drying the separated solid, grinding after drying to obtain raw crushed powder; mixing the raw crushed powder with powder of the same particle size produced in the crushing process, and then using concentrated sulfuric acid for secondary pickling, after pickling, rinsing with water, solid-liquid separation and drying in sequence;
[0010] S3, adding purified graphite powder, carbon black powder and SiC powder of the same particle size to the dried raw powder to mix to obtain a mixed powder; the mixed powder includes 30-45wt% of purified graphite powder, 15-20wt% of carbon black powder and 7-15wt% of SiC powder and the rest of the raw powder;
[0011] S4, adding 0.8-1.5% of methyl methacrylate, 1-3% of hydroxy polydimethylsiloxane and a binder to the mixed powder, stirring continuously and evenly during the mixing process to ensure that the binder can fully wrap the mixed powder particles, and then molding the mixed carbon binder mixture to obtain a semi-finished graphite recarburizer;
[0012] S5, subjecting the formed graphite recarburizer semi-finished product to high-temperature graphitization treatment, wherein the high-temperature graphitization treatment is performed by heating to 2500-3000° C. in a non-oxidizing atmosphere to perform a graphitization reaction so that a stable graphite structure is formed between the carbon powder particles;
[0013] S6. After the graphitization treatment is completed, the product is cooled, cleaned and dried to remove surface impurities and residual binder to obtain the final graphite recarburizer product.
[0014] As a further limitation, the raw crushed materials are graphite crushed materials, graphite offcuts, graphitized petroleum coke generated in the production process of carbon production enterprises, and graphite residual electrodes generated in the production and use process of recycled lithium batteries; the fixed carbon content of the raw crushed materials is ≥70%, the volatile matter is ≤10%, and the ash content is ≤20%.
[0015] As a further limitation, in step S1, when the raw carbon powder is cleaned, the raw powder is put into an ethanol aqueous solution and ultrasonically assisted in cleaning. After the cleaning is completed, the scum is filtered out, and the settled material is rinsed with water, and the solid and liquid are separated after rinsing, thus completing the cleaning operation.
[0016] As a further limitation, in step S1 and step S2, when the drying operation is performed, the corresponding material is sent to a drying box, the drying temperature is set at 100-180° C., and the drying is continued for 2-4 hours until the moisture content of the material drops below 5%.
[0017] As a further limitation, in step S2, the mass fraction of dilute hydrochloric acid or dilute sulfuric acid used in the initial pickling is 35-45%, and the pickling treatment time is 1-3 hours; the mass fraction of concentrated sulfuric acid used in the secondary pickling is 75-80%, and the pickling treatment time is 0.5-2 hours.
[0018] As a further limitation, in step S2, the raw crushed powder after two acid washings and drying treatments is sequentially subjected to magnetic separation and color separation to screen out metallic impurities and non-metallic impurities therein.
[0019] As a further limitation, in step S3, a fluxing agent is also added, and the fluxing agent is borax or calcium fluoride, and the addition amount is 0.5% to 2% of the total mass of the mixed powder;
[0020] After adding the fluxing agent, the semi-finished graphite recarburizer needs to be calcined at a high temperature of 1500°C to 1800°C before high-temperature graphitization treatment, and the duration is about 2 to 4 hours.
[0021] As a further limitation, in step S4, the binder used is asphalt or coal tar:
[0022] In the molding stage, if the corresponding graphite recarburizer semi-finished product is a block or granular material made by pressing or extrusion molding, the amount of the corresponding binder is 5-10% of the mass of the mixed powder;
[0023] In the molding stage, if the corresponding graphite recarburizer semi-finished product is a granular material formed by a rotary drum granulation method, the amount of the corresponding binder is 3-5% of the mass of the mixed powder.
[0024] As a further limitation, the graphite recarburizer product obtained by the method has a carbon content of 80-90% and a water content of less than 2%.
[0025] Beneficial effects: The present invention relates to a method for preparing a graphite recarburizer by utilizing carbon raw materials. The method has the advantages of simple process, mild reaction conditions and relatively low manufacturing cost. It can significantly improve the economic value of carbon raw materials and convert carbon raw materials originally used as low-value fuel or only for reducing production costs into high-value-added graphite recarburizers. This not only reduces the amount of high-quality purified graphite powder used and reduces production costs, but also enables the final product to achieve efficient resource utilization and environmental sustainable development while meeting industrial needs.
[0026] The method effectively removes impurities in the raw carbon powder by pre-treating the raw carbon powder, and ensures the purity and quality of the raw powder through special pickling, modification and drying processes. This enhances the surface activity and processability of the graphite recarburizer. The graphite recarburizer prepared by mixing the treated raw powder as one of the raw materials with purified graphite powder, carbon black powder and SiC powder has a higher fixed carbon content and a lower impurity content, which not only improves the carbon absorption rate and carbon recovery rate, but also ensures that the graphite recarburizer can better combine with the metal melt during use, thereby improving the recarburization effect and the fluidity of the melt. DETAILED DESCRIPTION
[0027] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0028] In the following embodiments, it will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as the meaning in the context of the prior art, and will not be interpreted with an idealized or overly formal meaning unless defined as herein.
[0029] In different embodiments, the steps of preparing a graphite electrode by using raw carbon to prepare a graphite recarburizer are as follows:
[0030] In Example 1, the graphite recarburizer is obtained by the following method:
[0031] First, carbon raw crushed materials are collected from carbon production enterprises. These raw crushed materials mainly come from unqualified products and waste materials generated in the production process of carbon products. The corresponding raw crushed materials have a fixed carbon content of 82%, volatile matter ≤10%, and ash content ≤10%. These raw crushed materials are preliminarily cleaned, and the raw crushed powder is put into a 35% ethanol aqueous solution by mass, and ultrasonic-assisted cleaning is used for 30 minutes to remove dust and impurities on the surface. After cleaning, the raw crushed powder is filtered to remove scum, and the static sediment is washed with water, and then solid-liquid separation is performed to complete the cleaning operation.
[0032] Subsequently, the washed raw powder is sent to a drying box set at 150°C for 2 hours until the moisture content of the material drops to 3%. After drying, the raw powder is placed in a crusher to obtain carbon raw powder with a particle size of 50 to 80 meshes.
[0033] The raw carbon materials were initially pickled with 35% by mass dilute hydrochloric acid for 2 hours. After the pickling, they were rinsed with water and solid-liquid separation was performed. The separated solids were then dried in a drying oven set at 150°C for 2 hours. The dried materials were then ground to obtain raw powder that passed a 200-300 mesh sieve.
[0034] The raw crushed powder is mixed with the powder of the same particle size produced during the crushing process, and is pickled twice with 78% concentrated sulfuric acid by mass for 1 hour. After the second pickling, it is rinsed with water again, the solid and liquid are separated, and dried in the same process as above.
[0035] After two acid washes and drying, the raw powder is sequentially magnetically separated and color-sorted to remove metal and non-metallic impurities to improve the purity of the final product. During the magnetic separation process, a magnetic separator with a magnetic field strength of 0.1 to 0.5 T is used to effectively separate ferromagnetic impurities. During the color sorting process, a high-resolution color sorter is used to further screen out non-metallic impurities such as quartz and clay based on the color differences of the materials. The purity of the raw powder treated by magnetic and color sorting is significantly improved, laying a good foundation for subsequent graphitization treatment.
[0036] The dried raw powder is mixed with purified graphite powder, carbon black powder and SiC powder in the proportions of 37.5wt%, 35wt%, 17.5wt% and 10wt% to obtain a mixed powder. The ratio of the mixed powder is carefully designed according to the performance requirements of the graphite recarburizer. The addition of purified graphite powder can significantly improve the graphitization degree and carbon content of the product, the carbon black powder helps to improve the conductivity and thermal stability of the product, and the addition of SiC powder can enhance the mechanical strength and oxidation resistance of the product. By accurately controlling the proportion of each component, a graphite recarburizer with excellent performance can be prepared. Methyl methacrylate accounting for 1% of the mass of the mixed powder, hydroxypolydimethylsiloxane accounting for 2% of the mass of the mixed powder and asphalt accounting for 8% of the mass of the mixed powder are added to the mixed powder as a binder for mixing. The mixing process is continuously and evenly stirred to ensure that the binder can fully wrap the mixed powder particles, and then the mixed carbon binder mixture is molded into a block graphite recarburizer semi-finished product by molding.
[0037] Among them, methyl methacrylate, as a binder, can form a good bond with other components in the mixed powder, improving the strength and stability of the semi-finished product after molding. Hydroxypolydimethylsiloxane, as an adhesion promoter, further enhances the bonding effect and ensures that during the high-temperature graphitization process, the mixed powder particles can be tightly bonded to form a stable graphite structure.
[0038] The formed graphite recarburizer semi-finished product is subjected to high-temperature graphitization treatment, heated to 2800°C in a non-oxidizing atmosphere, and calcined for 200 hours to complete the graphitization reaction, so that a stable graphite structure is formed between the carbon powder particles. After the graphitization treatment is completed, the product is cooled, cleaned and dried. Cooling, cleaning and drying are important links to ensure the purity and quality of the final product. The cooling process needs to be carried out slowly to avoid excessive internal stress of the product due to a sudden drop in temperature and cracks. During the cleaning process, deionized water is used to thoroughly remove surface impurities and residual binder. Finally, drying is performed to ensure that there is no water residue on the surface of the product, thereby obtaining a dry and pure block graphite recarburizer product.
[0039] In order to further improve the quality of graphite recarburizer products, the dried graphite recarburizer products can be reused with an impurity removal device to better filter the dust and impurities on the surface of the recarburizer, thereby avoiding the problem of reduced recarburization effect due to insufficient impurity removal of large particles of recarburizer.
[0040] Through the above embodiment, a graphite recarburizer with high fixed carbon content and low impurity content can be obtained, wherein the carbon content is 85% and the water content is less than 1%. The graphite recarburizer exhibits excellent recarburization effect in the steelmaking production process, and the carbon absorption rate can be as high as 95% or more, meeting the demand for high-quality steel smelting. In addition, the method effectively utilizes the waste of carbon raw materials, realizes the recycling of resources, reduces production costs, and has good economic and environmental benefits.
[0041] In Example 2, the graphite recarburizer is obtained by the following method:
[0042] The raw carbon powder as raw material is also the unqualified product and waste produced in the production process of carbon products. The fixed carbon content of the raw powder is 85%, the volatile matter is ≤8%, and the ash content is ≤7%. It is cleaned with ultrasonic in a 40% ethanol aqueous solution by mass fraction. After cleaning, the cleaned raw powder is dried until the moisture content of the material is reduced to 2%. After drying, the raw powder is put into a crusher to be crushed to obtain carbon raw powder with a particle size of 60 to 90 meshes.
[0043] The raw carbon powder was initially pickled with 42% by mass of dilute sulfuric acid. The pickling process lasted for 2.5 hours. After pickling, it was rinsed and solid-liquid separated. The separated solid was dried and ground to make raw powder of 200-300 mesh. The raw powder was mixed with the powder of the same particle size produced during the crushing process, and a secondary pickling was performed with 78% by mass of concentrated sulfuric acid. The pickling time was 1.5 hours. After the secondary pickling, it was rinsed with water again, solid-liquid separated, and dried and post-processed with the same process as above to obtain raw powder.
[0044] The raw powder is mixed with purified graphite powder, carbon black powder and SiC powder in the proportions of 40wt%, 30wt%, 15wt% and 15wt% to obtain a mixed powder, methyl methacrylate accounting for 1.2% of the mass of the mixed powder, hydroxypolydimethylsiloxane accounting for 2.5% of the mass of the mixed powder and coal tar accounting for 4% of the mass of the mixed powder are added to the mixed powder as a binder, and after mixing, a spherical graphite recarburizer semi-finished product is produced by a rotary drum granulation method.
[0045] The formed graphite carburizer semi-finished product is subjected to high-temperature graphitization treatment, heated to 2900°C in a non-oxidizing atmosphere, and calcined for 220 hours to complete the graphitization reaction. After the graphitization treatment is completed, the product is cooled, cleaned and dried to obtain a graphite carburizer product, and the graphite carburizer product is screened and classified to obtain graphite carburizer spherical products with different particle sizes.
[0046] Through the above embodiments, a graphite recarburizer with high fixed carbon content and low impurity content can be obtained, wherein the carbon content is 87% and the water content is less than 1%. The graphite recarburizer exhibits excellent recarburization effect in the steelmaking production process, and the carbon absorption rate can be as high as 97% or more, which can also meet the needs of high-quality steel smelting.
[0047] In Example 3, the graphite recarburizer is obtained by the following method:
[0048] The raw carbon powder used as raw material is the graphite residual electrode produced in the production and use process of lithium batteries. The fixed carbon content of the corresponding raw powder is 90%, the volatile matter is ≤5%, and the ash content is ≤5%. Ultrasonic assisted cleaning is carried out in a 45% ethanol aqueous solution by mass for 45 minutes to ensure that the impurities on the surface are completely removed. After cleaning, the raw powder is dried until the moisture content drops to 3%. After drying, the raw powder is placed in a crusher to obtain carbon raw powder with a particle size of 70 to 100 meshes.
[0049] The raw carbon powder was initially pickled with 45% by mass of dilute sulfuric acid for 3 hours. After pickling, it was rinsed and solid-liquid separated. The separated solid was dried and ground to produce raw powder of 250-350 mesh. The raw powder was mixed with the powder of the same particle size produced during the crushing process and pickled for a second time with 80% by mass of concentrated sulfuric acid for 2 hours. After the second pickling, it was rinsed again with water, solid-liquid separated, and dried and post-processed with the same process as above to obtain raw powder.
[0050] Raw powder, purified graphite powder, carbon black powder and SiC powder are mixed in the proportion of 30wt%, 42wt%, 18wt% and 10wt% to prepare a mixed powder. Subsequently, 1.5% of methyl methacrylate, 3% of hydroxy polydimethylsiloxane, 6% of asphalt as a binder and 1% of borax as a flux are added to the mixed powder. After being fully mixed, a strip-shaped graphite recarburizer semi-finished product is produced by extrusion molding technology.
[0051] The formed graphite carburizer semi-finished product is first calcined at a high temperature of 1800°C for 3.5 hours. During the calcination process, the fluxing agent helps to lower the melting point of the material and promote the graphitization reaction, thereby improving the graphitization degree of the carburizer. After the calcination treatment is completed, it is cooled to room temperature with the furnace, and then subjected to high-temperature graphitization treatment, heated to 3000°C in a non-oxidizing atmosphere, and calcined for 240 hours to complete the graphitization reaction. After the graphitization treatment is completed, the product is cooled, cleaned and dried to obtain a graphite carburizer product, and the graphite carburizer product is screened and classified to obtain a graphite carburizer strip finished product with different lengths and diameters.
[0052] Through the above embodiments, a graphite recarburizer with high fixed carbon content and low impurity content can be obtained, wherein the carbon content is 89% and the water content is less than 1%. The graphite recarburizer exhibits excellent recarburization effect in the steelmaking production process, and the carbon absorption rate can be as high as 98% or more, meeting the demand for high-quality steel smelting.
[0053] It can be seen from the above embodiments that the present invention provides a method for preparing a graphite recarburizer by using raw carbon powder, which can not only effectively utilize industrial waste and reduce production costs, but also prepare a graphite recarburizer with excellent performance to meet the needs of industrial applications.
[0054] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a graphite recarburizer using raw carbon, characterized in that: The method specifically comprises the following steps: S1, washing the collected raw carbon, and drying it after washing to remove floating dust and surface impurities; S2, crushing the dried carbon raw material into crushed materials, firstly using dilute hydrochloric acid or dilute sulfuric acid for primary pickling, after pickling, rinsing with water and solid-liquid separation, drying the separated solid, grinding after drying to obtain raw crushed powder; mixing the raw crushed powder with powder of the same particle size produced in the crushing process, and then using concentrated sulfuric acid for secondary pickling, after pickling, rinsing with water, solid-liquid separation and drying in sequence; S3, adding purified graphite powder, carbon black powder and SiC powder of the same particle size to the dried raw powder to mix to obtain a mixed powder; the mixed powder includes 30-45wt% of purified graphite powder, 15-20wt% of carbon black powder and 7-15wt% of SiC powder and the rest of the raw powder; S4, adding 0.8-1.5% of methyl methacrylate, 1-3% of hydroxy polydimethylsiloxane and a binder to the mixed powder, stirring continuously and evenly during the mixing process to ensure that the binder can fully wrap the mixed powder particles, and then molding the mixed carbon binder mixture to obtain a semi-finished graphite recarburizer; S5, subjecting the formed graphite recarburizer semi-finished product to high-temperature graphitization treatment, wherein the high-temperature graphitization treatment is performed by heating to 2500-3000° C. in a non-oxidizing atmosphere to perform a graphitization reaction so that a stable graphite structure is formed between the carbon powder particles; S6. After the graphitization treatment is completed, the product is cooled, cleaned and dried to remove surface impurities and residual binder to obtain the final graphite recarburizer product.
2. The method for preparing a graphite recarburizer by using raw carbon according to claim 1, characterized in that: The raw crushed materials are graphite crushed materials, graphite cuttings, graphitized petroleum coke and graphite residual electrodes generated in the production and use process of carbon production enterprises, and recycled lithium batteries; the fixed carbon content of the raw crushed materials is ≥70%, the volatile matter is ≤10%, and the ash content is ≤20%.
3. The method for preparing a graphite recarburizer by using raw carbon according to claim 1, characterized in that: In step S1, when the raw carbon powder is cleaned, the raw carbon powder is put into an ethanol aqueous solution and cleaned with ultrasound. After the cleaning is completed, the scum is filtered out, and the settled material is rinsed with water, and the solid and liquid are separated after the rinsing, thus completing the cleaning operation.
4. The method for preparing a graphite recarburizer by using raw carbon according to claim 1, characterized in that: In step S1 and step S2, when the drying operation is performed, the corresponding material is sent to a drying box, the drying temperature is set at 100-180° C., and the drying is continued for 2-4 hours until the moisture content of the material drops below 5%.
5. The method for preparing a graphite recarburizer by using raw carbon according to claim 1, characterized in that: In step S2, the mass fraction of dilute hydrochloric acid or dilute sulfuric acid used in the initial pickling is 35-45%, and the pickling treatment time is 1-3 hours; the mass fraction of concentrated sulfuric acid used in the secondary pickling is 75-80%, and the pickling treatment time is 0.5-2 hours.
6. The method for preparing a graphite recarburizer by using raw carbon according to claim 1, characterized in that: In step S2, the raw powder after two acid washings and drying is subjected to magnetic separation and color separation in sequence to screen out metal impurities and non-metal impurities therein.
7. The method for preparing a graphite recarburizer using raw carbon according to claim 1, characterized in that: In step S3, a fluxing agent is also added, wherein the fluxing agent is borax or calcium fluoride, and the amount added is 0.5% to 2% of the total mass of the mixed powder; After adding the fluxing agent, the semi-finished graphite recarburizer needs to be calcined at a high temperature of 1500°C to 1800°C before high-temperature graphitization treatment, and the duration is about 2 to 4 hours.
8. The method for preparing a graphite recarburizer by using raw carbon according to claim 1, characterized in that: In step S4, the binder used is asphalt or coal tar: In the molding stage, if the corresponding graphite recarburizer semi-finished product is a block or granular material made by pressing or extrusion molding, the amount of the corresponding binder is 5-10% of the mass of the mixed powder; In the molding stage, if the corresponding graphite recarburizer semi-finished product is a granular material formed by a rotary drum granulation method, the amount of the corresponding binder is 3-5% of the mass of the mixed powder.
9. The method for preparing a graphite recarburizer using raw carbon according to claim 1, characterized in that: The carbon content of the graphite recarburizer product prepared by the method is 80-90%, and the water content is less than 2%.